2021
DOI: 10.1002/ente.202000968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Optimized Electrode Surface Roughness and Solid Electrolyte Interphase on Lithium Dendrite Growth

Abstract: Lithium metal is an ideal anode material for high‐energy‐density rechargeable batteries. However, harmful dendrites lead to short circuit and cause safety hazards. Herein, a fundamental study on increasing the roughness of the electrode and its influence on the behaviors of lithium dendrites by combining experiment and simulation is presented. Various aspects of the growth behaviors of lithium dendrite on the electrode surface are investigated with consideration of the overpotential, roughness, and the solid e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…4(c) and (d)), this phenomenon was attributed to the different electrode surface roughness and solid electrolyte interface exhibited by graphite and platinum, which will affect the growth of dendrites. 28 The particles size of both types of cathode depositions was in the micrometre range.…”
Section: Resultsmentioning
confidence: 98%
“…4(c) and (d)), this phenomenon was attributed to the different electrode surface roughness and solid electrolyte interface exhibited by graphite and platinum, which will affect the growth of dendrites. 28 The particles size of both types of cathode depositions was in the micrometre range.…”
Section: Resultsmentioning
confidence: 98%
“…2. This protrusion follows a Gaussian curve and is expressed as: Note that, in general, this type of schematic has been widely used 24,44,[50][51][52][53][54][55] and studied for chemo-mechanics models, displacement models, and dendrite studies, but the movement of the interface with cycling should be better studied, particularly for mass and charge conservation. Further, the motion of the lithium surface, which is modeled as a moving boundary, will induce velocities in the liquid electrolyte owing to the no-slip condition at the electrode/electrolyte interface.…”
Section: "Moving Boundary" Model Formulation For Lithium Metal Batteriesmentioning
confidence: 99%
“…The SEI formed on the Li metal surface by some complex reactions, which has a certain ion conductivity, also plays a crucial role in the mass-transfer process of Li-ions and the kinetics of the Li deposition process. [36][37][38] Shi et al 39 found that the Li-ion diffusion through the SEI layer is the rate-determining step. Nevertheless, the native SEI has low conductivity, inhomogeneity, poor mechanical and electrochemical stability which can be damaged easily.…”
mentioning
confidence: 99%